Cyclic resistance evaluation of marine clay based on CPTu data: a case study of Shaba Wind Farm - Wu, Qi; Zhu, En-ci; Xiao, Xing; Li, Yuan-xi; Chen, Guo-xing (Frontiers in Marine Science, 2024)
The offshore wind farm industry has recently experienced significant global growth. This study presents a thorough site investigation and analysis of the cyclic resistance of marine clay for offshore foundation design, using the Shaba wind farm in southern China as a case study. In-situ cone penetrometer (CPTu) tests and borehole sampling are conducted to explore the geotechnical characteristics of the soils. However, the soil conditions are characterized by multiple layers and complex sedimentary components. The classification and mechanical properties, such as water content and cyclic resistances, are compared through CPTu interpretation and laboratory tests. The findings indicated that a single physical indicator cannot determine cyclic resistance. In addition, the well-established method in existing literature proved unsuitable for marine clay. Consequently, multiple regression analysis shows that a linear relationship exist between cyclic resistance and depth-corrected CPTu index [EXP(qE/fs)0.3/H], hence a new evaluation method is developed to predict the cyclic resistance of marine clay based on CPTu data. This research aims to provide more reliable guidance for geotechnical investigations, supporting the rapid expansion of offshore wind farms.